Does the Quality of Early Childhood Education and Care Centers Mitigate the Risk of Externalizing Problems? A~Genetic-Sensitive Study of Preschoolers in Germany - Bastian Mönkediek; Pia Schober; Martin Diewald; Harald Eichhorn; C. Katharina Spiess (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
This paper examines the extent to which quality characteristics of early childhood education and care (ECEC) experienced at ages~4–6 influence externalizing problems at ages~6–8. Based on a~random sample of 713 same-sex twins (55% female, 41% with a migration background) in 364 ECEC centers in Germany, the paper not only distinguishes between detailed ECEC quality characteristics but additionally investigates whether these characteristics affect the relevance of genetic and environmental influences on externalizing problem behavior. Results demonstrate that with educators' further training and the child–staff ratio only a few specific ECEC quality indicators moderate the relevance of genetic and environmental influences. In particular, further training of educators reduces genetic contributions to externalizing problems in children. Although there was also evidence for gene–environment correlation owing to selection into ECEC centers with an unfavorable child–staff ratio, the findings suggest that improving educators' training is the most promising way of counteracting externalizing problems.
Keywords: 300; Germany; Behavioral problems; Childcare centers; Quality; Twin study; Deutschland; Verhaltensauffälligkeiten; Kindertagesstätten; Qualität; Zwillingsstudie